Trades access common core. Line C, Tools and equipment, Competency C-1, Describe common hand tools and their uses - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Hand tools are used in almost every trade, but many of them have particular applications in a specific trade. It is likely you have used some of these tools already at work, at school, or at home, but this may be the first time you have had the chance to study some of the tools' designs and applications in detail. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line C - Tools and Equipment. C-1 Describe Common Hand Tools and Their Uses, C-2 Describe Common Power Tools and Their Uses, C-3 Describe Rigging and Hoisting Equipment, C-4 Describe Ladders and Platforms."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Tools -- Textbooks; Electronic books